From ontological to relational: A scoping review of conceptions of dignity invoked in deliberations on medically assisted death - Isabelle Martineau; Naïma Hamrouni; Johanne Hébert (BMC Medical Ethics, 2024)
Abstract Background Dignity is omnipresent in Western ethics, but it also provokes dissension and controversy. One of the most striking examples is the debate on medically assisted death, where dignity is invoked to support antagonistic positions. While some authors conclude that the concept is useless as an ethical reference, many others invite us to deepen our analysis from a multidimensional perspective, to enrich it and make it useful. This scoping study is intended to provide an overview of the different conceptions of dignity used in the assisted dying debate, to better grasp the multiple facets of the concept. Methods The Joanna Briggs Institute's JBI Manual for Evidence Synthesis guided the scoping review. Key words were based on the researchers' expertise and were used to identify relevant literature in French and English. Eleven databases covering the last six decades were consulted. Initially, 2,071 references were found in the databases. After excluding duplicates, screening titles, abstracts, and full texts, and after a specific literature search on the concept of relational dignity, 156 papers were found to match the identified inclusion criteria. Results The literature highlights the stark confrontation between two dominant conceptions of dignity: ontological and autonomist. However, a lesser-known conceptualization of dignity integrates these two perspectives, underlining the relational and social dimensions of dignity. As a result, dignity emerges as a dynamic, experiential, and dialogical concept, that modulates itself according to circumstances. This raises the possibility of breaking through the binary debate and questioning the current frameworks that define dignity. Conclusions This multidimensional conceptualization of dignity could lead to a more complete and nuanced understanding of the concept, as well as open richer normative horizons regarding the issue of medically assisted death.